Current collector including metallized film
By using a current collector structure of a biaxially oriented polymer base layer and metal layer in lithium-ion batteries, the problems of reduced adhesion and insufficient mechanical strength of the existing current collector at high temperatures are solved, and a lighter and thinner current collector is achieved, reducing the total mass and size of the battery, while increasing the energy density.
Patent Information
- Application Number
- CN202280034637.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-13
- Filing Date
- 2022-05-13
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-05-13
AI Technical Summary
Existing metal foil current collectors have risks of short circuit and overheating in lithium-ion batteries, and their thickness negatively affects the quality and size of the battery, making it difficult to provide a thinner current collector that does not affect mechanical strength.
The biaxially oriented polymer substrate layer and the first and second metal layers formed thereon are used to ensure that the polymer substrate layer exhibits positive thermal expansion at high temperatures and to increase the adhesion between the metal layer and the polymer substrate layer by optimizing the layer structure and deposition processes.
It realizes the mechanical strength and conductivity of the current collector under high temperature conditions, avoids the risks of short circuit and overheating, while reducing the total mass and size of the battery and improving the energy density.
Smart Images

Figure BDA0004543059940000211 
Figure BDA0004543059940000221 
Figure BDA0004543059940000231
Abstract
Description
[0001] The present invention relates to polymer films for current collectors, current collectors and other articles made therefrom, and methods for making the same. In particular, the present invention relates to current collectors for batteries, especially lithium-ion batteries.
[0002] Lithium-ion batteries are widely used in the field of rechargeable batteries, which will continue to grow in the foreseeable future, partly due to the growing demand for consumer electronics and renewable energy storage. During the operation of the battery (i.e., during charging and discharging), lithium ions are transferred between the anode material and the cathode material. Commercially available lithium-ion batteries generally contain a metal foil current collector, wherein the metal foil is placed in contact with each of the active solid electrodes. Generally, an aluminum-based foil is used as a cathode current collector and is arranged to contact the cathode, while a copper-based foil is used as an anode current collector and is arranged to contact the anode. In some arrangements, the cathode material may be coated on the cathode current collector, and / or the anode material may be coated on the anode current collector.
[0003] However, there are problems with such existing metal foil current collectors. First, the metal foil current collector has a high conductivity, which can cause excessive current in the entire battery, resulting in short circuits and overheating thermal runaway, which may cause fire. Secondly, the metal foil current collector is relatively thick, dense and heavy (usually more than 12 μm thick), and therefore contributes a lot to the total mass of the battery. It is desirable to provide a thinner and / or lighter current collector in order to increase the energy density and minimize the size and mass of the battery. However, it is challenging to provide a thinner current collector without adversely affecting its mechanical strength. To this end, metallized polymer film current collectors have been developed. Such a current collector contains an insulating or dielectric polymer substrate layer and a conductive metal layer on its surface. As is known in the art, such a current collector acts as an electrochemical fuse that is disconnected under a predetermined thermal and / or electrical load to avoid excessive current and thermal runaway. The metal layer is usually formed by a metal deposition process, which may require multiple deposition steps. During the metal deposition process and during subsequent battery fabrication, the current collector (and the polymer substrate layer within the current collector) are exposed to elevated temperature conditions for a long time, which may cause film overheating and permanent film damage, such as deformation and wrinkling, and thus loss of adhesion between the metal layer and the polymer substrate layer.
[0004] It is an object of the present invention to solve one or more of the above problems. In particular, it is an object of the present invention to provide an improved current collector for a battery, preferably for a lithium ion battery. A particular object of the present invention is to provide such a current collector, which exhibits improved adhesion between the polymer substrate layer and the metal layer, especially after prolonged exposure to elevated temperatures, such as during manufacturing, subsequent fabrication steps and / or end use. Another specific object of the present invention is to provide a current collector that at least maintains and preferably improves the energy density of existing metal foil current collectors.
[0005] According to a first aspect of the present invention, a current collector is provided, comprising a biaxially oriented polymer substrate layer and a first metal layer on one side of the polymer substrate layer, wherein the polymer substrate layer exhibits positive thermal expansion (and preferably not more than 3.0%) in each of the transverse direction (TD) and the mechanical direction (MD) at 200°C in air, wherein the polymer substrate layer has a thickness of not more than 12 μm, and wherein the first metal layer has a thickness of not more than 1000 nm.
[0006] Preferably, the current collector further comprises a second metal layer, wherein the first metal layer and the second metal layer are on opposite sides of the polymer substrate layer, and wherein the layer sequence is first metal layer / polymer substrate layer / second metal layer. The second metal layer, if present, has a thickness of no more than 1000 nm.
[0007] The inventors have unexpectedly discovered that such current collectors exhibit excellent resistance to delamination between the biaxially oriented polymer substrate layer and the first and second metal layers (if present), even after prolonged exposure to elevated temperatures. This is particularly advantageous in the field of lithium-ion batteries, which are easily subjected to such conditions during manufacture and use.
[0008] The first metal layer and the second metal layer (if present) are the outermost layers of the current collector.
[0009] Therefore, the current collector comprises at least two layers. Preferably, the first metal layer (A) is directly arranged on the first surface of the polymer substrate layer (B) to form an AB layer structure, i.e. wherein there is no intervening layer between the metal layer and the polymer substrate layer, so in this embodiment, the current collector consists of two layers.
[0010] Preferably, the current collector comprises at least three layers. Preferably, the first metal layer (A) is directly disposed on a first surface of the polymer substrate layer (B), and the second metal layer (C) is directly disposed on a second opposite surface of the substrate layer to form an ABC layer structure, i.e. wherein there is no intervening layer between the metal layer and the polymer substrate layer, so that in this embodiment, the current collector consists of three layers.
[0011] The substrate layer is a self-supporting film, which means a film that is capable of existing independently without a supporting substrate.
[0012] The term polymer as used herein refers to a polymer or a copolymer.
[0013] Thermoplastic polymer materials are preferred. Such materials include homopolymers or copolymers of 1-olefins such as ethylene, propylene and but-1-ene; polyamides; polycarbonates; PVC; PVA; polyacrylates; cellulose and polyesters. Polyolefins and polyesters are preferred, especially polyesters, especially linear polyesters.
[0014] The term polyester as used herein refers to a homopolyester or copolyester derived from one or more diols (at least one of which is an aliphatic diol) and one or more dicarboxylic acids (at least one of which is an aromatic dicarboxylic acid). Suitable dicarboxylic acids include terephthalic acid, isophthalic acid, phthalic acid; 2,5-, 2,6- or 2,7-naphthalene dicarboxylic acid; succinic acid; sebacic acid; adipic acid; azelaic acid; 4,4'-biphenyl dicarboxylic acid; hexahydroterephthalic acid or 1,2-bis-p-carboxyphenoxyethane (optionally containing a monocarboxylic acid such as pivalic acid). Suitable diols include aliphatic diols and alicyclic diols such as ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol and 1,4-cyclohexanedimethanol. Preferably, the aromatic dicarboxylic acid is selected from terephthalic acid and 2,5-, 2,6- or 2,7-naphthalene dicarboxylic acid, preferably from terephthalic acid and 2,6-naphthalene dicarboxylic acid. Preferably, the aliphatic diol is ethylene glycol.Preferably, the polyester is a homopolyester.
[0015] Preferred polyethylene terephthalate (PET) and polyethylene naphthalate (PEN) polyesters may optionally contain relatively small amounts (preferably less than 10 wt. % or less than 5 wt. %) of one or more residues derived from other dicarboxylic acids and / or diols as one or more comonomers. Other dicarboxylic acids include isophthalic acid, phthalic acid, 1,4-, 2,5- or 2,7-naphthalenedicarboxylic acid, 4,4'-biphenyldicarboxylic acid, hexahydroterephthalic acid, 1,10-decanedicarboxylic acid and diols of the general formula C n H 2n The polyester preferably comprises an aliphatic dicarboxylic acid of (COOH)2 wherein n is 2 to 8, such as succinic acid, glutaric acid, sebacic acid, adipic acid, azelaic acid, suberic acid or pimelic acid. Other diols include aliphatic and alicyclic diols such as diethylene glycol, propylene glycol, dipropylene glycol, 1,3-propanediol, 1,4-butanediol and 1,4-cyclohexanedimethanol. Preferably, the polyester contains only one dicarboxylic acid, i.e. terephthalic acid or 2,6-naphthalene dicarboxylic acid, preferably terephthalic acid. Preferably, the polyester contains only one diol, i.e. ethylene glycol.
[0016] Preferred polyolefins are selected from polyethylene or polypropylene, preferably polypropylene.
[0017] Preferred polyamides are linear aliphatic polyamides, preferably selected from: nylon 6,6; nylon 6; nylon 6.66; nylon 6,10; nylon 6,4; and blends and mixtures thereof. Nylon 6 and nylon 6,6 are particularly preferred polyamides, with nylon 6,6 being most preferred.
[0018] Preferably, the polymer substrate layer is a PET film or a PEN film.
[0019] Polymer is the main component of polymer substrate layer, and accounts for at least 60 weight %, preferably at least 70 weight %, and preferably at least 80 weight % of the total weight of polymer substrate layer.For example, polymer can account for at least 85 weight %, at least 90 weight % or at least 95 weight % of the total weight of polymer substrate layer.
[0020] The polymer substrate layer may further be included in any other additives conventionally used in the manufacture of polymer films. Such conventional additives may exist in a smaller ratio, and are generally no more than 35% by weight, generally no more than 20% by weight, generally no more than 5% by weight, and generally no more than 2% by weight relative to the gross weight of the layer. Therefore, reagents such as particle fillers, hydrolysis stabilizers, antioxidants, UV stabilizers, crosslinking agents, dyes, lubricants, free radical scavengers, heat stabilizers, surfactants, slip agents, antiblocking agents, flame retardants, gloss modifiers, pro-degradants, viscosity modifiers and dispersion stabilizers may be appropriately incorporated. As is well known in the art, it is particularly useful to improve the processing and windability of the particle fillers during the manufacturing period. Particle fillers are generally granular inorganic fillers (such as calcium carbonate, clay, silicon dioxide, zeolite, silicone beads (such as functionalized polydimethylsiloxane), dicalcium phosphate, tricalcium phosphate, hollow microspheres, zeosphere, talcum powder, titanium dioxide, barium sulfate and barium titanate). Filler particle size distribution can be unimodal, bimodal and trimodal. Preferably, for unimodal, bimodal and trimodal distributions, the volume weighted average particle size (D (4,3) ) is in the range of 0.1 to 10 μm. Preferably, the filler particle size distribution is bimodal so that there are two maximum peaks. Preferably, the first maximum of the particles has a volume weighted average particle size (D (4,3) ), and the second maximum of the particles has a volume weighted average particle size (D (4,3) ). The particle size of the filler particles is suitably measured by laser diffraction. The particulate inorganic filler is present in relatively small amounts, typically less than 5.0 wt%, typically less than 2.0 wt%, and typically less than 1.0 wt%.
[0021] The formation of the polymer is readily achieved by conventional synthetic methods well known in the art. For example, polyesters may be prepared by a first step of direct esterification or transesterification followed by a second step of polycondensation. Preferably, the synthetic procedure further comprises a solid phase polymerization (SSP) step to increase the molecular weight of the polymer, as is well known in the art. Suitable solid phase polymerization techniques are disclosed, for example, in EP-A-0419400, the disclosure of which is incorporated herein by reference. Thus, SSP is generally carried out at a temperature below the crystalline melting point (T M )10-50℃ but above the glass transition temperature (T g ) (or above the highest glass transition temperature in the case where the polyester exhibits multiple glass transition temperatures). A dry nitrogen inert atmosphere or vacuum is used to prevent degradation. In a preferred embodiment, the solid phase polymerization is carried out at 220° C. and under vacuum for more than 16 hours.
[0022] The polyesters suitable for use in the present invention have an intrinsic viscosity of at least 0.5 dL / g, preferably at least 0.55 dL / g, preferably at least 0.6 dL / g, preferably at least 0.7 dL / g, preferably at least 0.8 dL / g.
[0023] The polymeric substrate layer is preferably a single layer film.
[0024] Advantageously, the film can and preferably is manufactured in air, i.e., the film is not manufactured (including the steps of extrusion, casting and stretching) under an atmosphere of an inert gas (such as nitrogen or a rare gas such as argon). Therefore, the polymer compositions and films described herein are thermally stable and do not require any special handling conditions, particularly an inert atmosphere, during manufacture or storage.
[0025] The formation of the film can be achieved by conventional extrusion techniques well known in the art. In general, the process comprises the steps of extruding a layer of molten polymer in a range suitable for the melting temperature of the polymer, for example, at a temperature in the range of about 270 to about 300°C (or generally not more than about 15°C, preferably not more than about 10°C, above the crystalline melting point of the polymer), and then rapidly quenching the extrudate to ensure that the polymer is quenched into an amorphous state. The quenched extrudate is then biaxially oriented by stretching in two mutually perpendicular directions in the film plane at a temperature above the glass transition temperature of the polymer to achieve a satisfactory combination of mechanical and physical properties. Biaxial orientation can be achieved by sequential or simultaneous biaxial orientation. In the present invention, it is advantageous to manufacture the film by simultaneous biaxial orientation, for example, in a tubular process, by extruding a thermoplastic polymer tube, subsequently quenching it, reheating it, and then expanding it by internal gas pressure to cause transverse orientation, and withdrawing it at a rate that will cause longitudinal orientation. Particularly suitable simultaneous biaxial orientation processes are disclosed in EP-2108673-A and US-2009 / 0117362-A1 , the disclosures of which are incorporated herein by reference.
[0026] Stretching is generally performed such that the size of the oriented film is 2 to 7 times, preferably 2 to 5 times, more preferably 2.5 to 4.5 times, more preferably 3.0 to 4.5 times, more preferably 3.0 to 4.0 times its original size in each stretching direction. Preferably, the film is stretched 3.2 to 3.6 times its original size in the machine direction (MD), and preferably 3.3 to 3.8 times its original size in the transverse direction (TD). Stretching is performed at a temperature above the T of the polymer composition. g The temperature is preferably higher than T g At least about 5°C higher, preferably at least about 15°C higher, and preferably at about T g +5℃ to about T g +75℃, preferably about T g +5℃ to about T g In the range of +30°C. Therefore, stretching is usually carried out at a temperature in the range of about 5 to about 155°C, preferably about 5 to about 145°C. When the polymer composition is PET, stretching is usually carried out at a temperature in the range of about 85 to about 110°C, preferably about 95 to about 100°C. In the case where the polymer composition is PEN, stretching is usually carried out at a temperature in the range of about 130 to about 155°C, preferably about 140 to about 145°C. It is not necessary to stretch equally in the machine and transverse directions, but it is preferred if balanced properties are desired.
[0027] The stretched film is then dimensionally stabilized. In a first step, the film is annealed under dimensional support (or restraint) to induce the polymer to reach the desired crystallinity. Temperatures of at least about 200° C. are preferred. Preferably, the temperature employed is above the glass transition temperature of the polymer but below its melting temperature (T M Within these constraints, the preferred annealing temperature is generally about 80°C below the melting temperature of the film (i.e., T M -80℃) to T M About 10℃ lower (T M -10°C), preferably about T M -70℃ to about T M -20°C. Therefore, the annealing temperature is suitably in the range of about 200 to about 245°C, preferably about 215 to about 245°C, preferably about 220 to about 245°C, preferably about 220 to about 240°C. The time for which the film is kept at this temperature is preferably in the range of 0 to 60 seconds, preferably 0.1 to 10 seconds, preferably 0.5 to 5 seconds, preferably 0.7 to 3 seconds.
[0028] After annealing under dimensional constraint, the film is then dimensionally relaxed in the transverse direction (TD) and the machine direction (MD). Dimensional relaxation can be achieved by sequential or simultaneous dimensional relaxation, preferably sequentially. The relaxation step is suitably an online relaxation step, i.e., a stage in a film production line. The film is relaxed by about 0.5 to about 5.0% in the transverse direction (TD) and the machine direction (MD), respectively, preferably by about 1.0 to about 4.0%, preferably by about 1.0 to 3.0%, preferably by about 1.0 to about 2.0%. The relaxation in the mechanical and transverse directions can be the same. However, if a balanced performance is desired, the relaxation in the mechanical and transverse directions is preferably different. In the relaxation step, the film is heated at a temperature preferably not higher than the temperature of the immediately preceding annealing step, and the MD and TD tensions are low. MD relaxation is controlled by reducing the speed of the film production line, while TD relaxation is controlled by reducing the distance between the film clips on the opposite transverse edges of the film, each of which results in a reduction in the tension experienced by the film in the relevant dimensions of this manufacturing stage. Temperatures of at least about 200° C. are preferred, preferably about 200° C. to about 250° C., preferably about 200° C. to about 245° C., preferably about 200° C. to about 240° C., preferably about 210° C. to about 230° C., preferably about 215° C. to about 230° C., preferably about 215° C. to 225° C. The duration of heating for the relaxation step will depend on the temperature employed, but is typically in the range of 0 to 30 seconds, preferably 0.1 to 10 seconds, preferably 0.4 to 4 seconds, preferably 0.9 to 3.8 seconds.
[0029] Preferably, a second relaxation step is then performed (in this case, the above relaxation step is referred to as the first relaxation step). The second relaxation step is implemented in a similar manner as described for the first relaxation step. A temperature of at least about 195°C is preferred, and a temperature of at least about 200°C is most preferred. The second relaxation step can be implemented at a temperature similar to the first relaxation step. Alternatively, the second relaxation step can be performed at a lower temperature than the first relaxation step, preferably at least about 5°C lower. Therefore, it is preferred that the second relaxation step is performed in the range of about 195°C to about 245°C, preferably about 195°C to about 240°C, preferably about 195°C to about 235°C, preferably about 195°C to about 230°C, preferably about 195°C to about 220°C, preferably about 195°C to about 215°C. The heating duration of the second relaxation step will depend on the temperature used, but is generally in the range of 0 to 30 seconds, preferably 0.1 to 10 seconds, preferably 0.4 to 3.5 seconds, preferably 0.7 to 3.0 seconds.
[0030] After the annealing step and the relaxation step, the film is rapidly cooled.
[0031] The inventors found that the resulting polymer film exhibits high dimensional stability at elevated temperatures and exhibits positive thermal expansion in the transverse direction (TD) and the mechanical direction (MD) at 200°C. Therefore, the thermal response of the polymer substrate layer in the mechanical direction and the transverse direction is consistent with the thermal response of the metal layer, and the current collector of the present invention exhibits high dimensional stability, and there is no deformation, warping or delamination during subsequent processing at elevated temperatures (e.g., during metal deposition or during subsequent battery formation). In contrast, the current collector of the prior art in which the polymer substrate layer is manufactured by the annealing and relaxation process described herein exhibits shrinkage and dimensional instability, and deformation during processing at subsequent elevated temperatures is observed, and poor resistance to delamination is exhibited.
[0032] Preferably, the polymer substrate layer exhibits a thermal expansion of greater than 0% to no more than 3.0%, preferably greater than 0% to no more than 2.0%, preferably 0.1% to 2.0%, preferably 0.2% to 1.5% in each of the transverse direction (TD) and the machine direction (MD) in air at 200° C. Preferably, the polymer substrate layer exhibits isotropic thermal expansion, i.e., the layer expands the same amount in TD and MD.
[0033] The inventors have found that manufacturing steps, particularly annealing and relaxation processes as described herein, can be performed so that the polymer substrate film exhibits isotropic thermal expansion. In particular, the dimensional relaxation in MD and TD during the relaxation process as described herein can be controlled. For example, the dimensional relaxation achieved in MD and TD can be different to offset any residual deformation in MD or TD produced by the previous manufacturing steps so that the final resulting polymer film exhibits balanced performance and therefore exhibits isotropic thermal expansion.
[0034] Preferably, the polymer substrate layer exhibits a positive coefficient of linear thermal expansion (CLTE) in each of the transverse direction (TD) and the machine direction (MD) in air in the range of 32°C to 200°C, preferably a positive CLTE of less than 20 x 10 -5 / ℃, preferably positive CLTE is less than 17x10 -5 / ℃, preferably positive CLTE is less than 10x 10 -5 / ℃, preferably positive CLTE is less than 9x 10 -5 / ℃, preferably positive CLTE is less than 8.5x 10 -5 / ℃.
[0035] The thickness of the polymer substrate layer is no more than 12.0 μm, preferably no more than 10.0 μm, preferably no more than 8.0 μm, preferably no more than 6.0 μm. The thickness of the polymer substrate layer is preferably at least 1.0 μm, preferably at least 2.0 μm, preferably at least 3.0 μm, preferably at least 4.0 μm. Therefore, the thickness of the polymer substrate layer is preferably 1.0 to 12.0 μm, preferably 2.0 to 8.0 μm, preferably 4.0 to 8.0 μm, preferably 4.0 to about 6.0 μm.
[0036] The first metal layer and the second metal layer (if present) are each formed by a metal conductive material. Preferably, the first and second metal layers comprise the same metal conductive material. Alternatively, the first and second metal layers may comprise different metal conductive materials. The metal conductive material is preferably selected from at least one of aluminum, copper, nickel, titanium, silver, nickel-copper alloy or aluminum-zirconium alloy. Preferably, the metal conductive material is aluminum or copper. In the case where the current collector is a cathode current collector, the first metal layer and the second metal layer (if present) preferably comprise aluminum. In the case where the current collector is an anode current collector, the first metal layer and the second metal layer (if present) preferably comprise copper.
[0037] Where the first and second metal layers (if present) comprise aluminium, preferably the polymeric substrate layer is a PET film. Where the first and second metal layers (if present) comprise copper, preferably the polymeric substrate layer is a PEN film.
[0038] The metal layer preferably comprises at least 90 wt. %, preferably at least 95 wt. %, preferably at least 98 wt. % and preferably at least 99 wt. % of the above-mentioned metal conductive material, the weight of the metal conductive material being the weight percentage relative to the total weight of the metal layer. In a preferred embodiment, the metal layer consists of the metal conductive material.
[0039] The metal layer exhibits a positive coefficient of thermal expansion. Preferably, the first metal layer and the second metal layer (if present) in the current collector of the present invention independently exhibit a thermal expansion of greater than 0% to no more than 2.0%, preferably greater than 0% to no more than 1.0%, preferably 0.25% to 0.75%, preferably 0.3% to 0.5% at 200°C in air. The metal layers in the current collector of the present invention each preferably exhibit isotropic thermal expansion, i.e., each layer expands the same amount in orthogonal directions, such as in directions corresponding to the machine dimensions and lateral dimensions of the polymer substrate layer. Preferably, the first metal layer and the second metal layer exhibit the same expansion as each other at 200°C.
[0040] Preferably, the ratio of the thermal expansion of the polymer substrate layer in the lateral direction at 200°C in air to the thermal expansion of each of the first and second metal layers at 200°C in air is 1:5 to 5:1, preferably 2:1 to 1:2, preferably 1.5:1 to 1:1.5, preferably 1.2:1 to 1:1.2:1, preferably about 1:1.
[0041] Preferably, the ratio of the thermal expansion of the polymer substrate layer in the machine direction at 200°C in air to the thermal expansion of each of the first and second metal layers in air at 200°C is 1:5 to 5:1, preferably 1.5:1 to 1:1.5, preferably 1.2:1 to 1:1.2, preferably about 1:1.
[0042] Preferably, the first metal layer and the second metal layer (if present) independently exhibit a thermal conductivity of about 10 x 10 -6 / ℃ to about 30x 10 -6 / ℃, preferably about 12x10 -6 / ℃ to about 18x 10 -6 / ℃ positive linear thermal expansion coefficient (CLTE).
[0043] Preferably, the thickness of each of the first metal layer and the second metal layer (if present) is independently in the range of about 50 nm to about 1000 nm, preferably about 100 nm to about 1000 nm, preferably about 100 nm to about 800 nm, preferably about 150 nm to about 700 nm.
[0044] The first metal layer and the second metal layer (if present) are each suitably deposited onto the polymer substrate layer. Any suitable deposition technique known in the art for making metallized films can be used, including at least one of vapor deposition and electroless plating. Preferably, the first metal layer and the second metal layer are independently deposited onto the polymer substrate layer by at least one of vapor deposition and electroless plating. The vapor deposition can be at least one of physical vapor deposition (PVD), virtual cathode deposition (VCD) or chemical vapor deposition (CVD).
[0045] Preferably, physical vapor deposition is selected from at least one of evaporative deposition and sputtering deposition. Evaporative deposition is preferably at least one of vacuum evaporation, thermal evaporation or electron beam evaporation techniques. Sputtering deposition is preferably magnetron sputtering. Suitable processes include, for example, plasma enhanced vapor deposition techniques, such as plasma enhanced electron beam evaporation techniques and plasma enhanced sputtering techniques.
[0046] Preferably, the metal layer is provided by thermal evaporation deposition, electron beam evaporation or virtual cathode deposition.
[0047] Typically, thermal evaporation deposition involves placing a polymer substrate and source material in a vacuum chamber. -4 The source material is heated at a low temperature of 200 psi (1000 Pa) until it evaporates. The evaporated source material particles are dispersed toward the substrate and condensed on the substrate surface to form a thin film. Typically, a resistive coil in the form of a powder or solid rod is subjected to a large direct current (preferably in the range of 100 to 150 mA for a period of 10 to 15 seconds) to generate heat for evaporating the source material. Suitable apparatus include those commercially available from Balzers AG (Liechtenstein) under the name "BAE 370" or equipment commercially available from Bühler and Applied Materials.
[0048] Generally, electron beam evaporation involves the use of high energy electrons in the form of an intense beam to evaporate a source material. A hot filament is used to thermionically emit electrons which, after acceleration, are used to evaporate the source material.
[0049] Typically, virtual cathode deposition includes providing a high voltage pulse to a virtual plasma cathode to generate a high energy density electron beam (preferably wherein the energy is greater than 100 MW / cm 2 The high energy density electron beam ablates the solid target so that a portion of the ablated target material (e.g., about 0.001 mm 3 ) forms a plasma. The plasma propagates toward the polymer substrate in the form of a plasma tank. The plasma tank can have a speed of up to about 50 km / s. The target material plasma condenses on the substrate surface to form a thin film. For example, 400 cm 2Each pulse can form a thin film with a thickness of up to 0.1 nm. Repeating high voltage pulses (e.g., a frequency of up to about 600 Hz) and / or using a device including multiple virtual cathode groups can cause the deposited film to grow until the desired thickness is reached. Suitable virtual cathode deposition methods and devices are known and include, for example, the methods and devices discussed in WO-2016 / 042530-A and US-2020 / 0095129-A, and the disclosures of the methods and devices are incorporated herein by reference.
[0050] The deposition technique may need to be performed in a single pass or multiple passes (e.g., two passes) to deposit a metal layer of desired thickness. Preferably, the deposition technique needs to be performed in a single pass, which is beneficial for improving manufacturing efficiency and minimizing exposure of the polymer substrate to elevated temperature conditions for a long time.
[0051] As will be appreciated by the skilled artisan, the current collector needs to exhibit electrical conductivity when disposed in a battery. Thus, although the polymer substrate layer imparts electrical insulation, electrical conductivity must be allowed between the outer surfaces of the current collector. For example, although the polymer substrate layer disposed between the first and second metal layers imparts electrical insulation, electrical conductivity must be allowed from the first metal layer to the second metal layer (if present).
[0052] In one embodiment referred to herein as arrangement 1, the current collector further includes at least one conductive tab connecting the first metal layer and the second metal layer so that the current collector exhibits conductivity from one surface thereof to another surface. Such conductive tabs are known in the art, for example, as disclosed in WO-2019 / 051123-A and US-10700339-B. Preferably, the tabs extend beyond the periphery of the current collector so that the tabs can connect the current collector to other components in the battery. Preferably, the tabs extend from the interior to the exterior of the lithium-ion battery so that the tabs can connect the battery to an external power source.
[0053] In another embodiment referred to herein as arrangement 2, the polymer substrate layer includes a channel extending from its first surface to a second opposite surface, wherein (i) the side of the channel is at least partially coated with at least one metal, and / or (ii) the channel is at least partially filled with at least one metal, preferably so as to produce a conductive path between the first metal layer and the second metal layer. Such a channel is known in the art and is disclosed, for example, in US-2019 / 0305320-A. The channel may have a pore size (e.g., diameter) in the range of about 1 μm to about 5 mm. The fraction of the surface area of the polymer substrate layer consisting of channel holes is generally about 0.01 to about 10%. Such a channel allows further reduction of the weight of the battery, as well as improvement of its electrochemical performance, such as charge-discharge rate and cycle life. The metal is preferably deposited during the metal deposition step for depositing the first and second metal layers described above, and preferably a virtual cathode deposition technique. Arrangement 2 is further shown in FIG. 1. Figure 1A The current collector arrangement is shown in cross section. The current collector (10) has a biaxially oriented substrate layer (B) (3), a first metal layer (A) (1) and a second metal layer (C) (2), wherein the current collector has an ABC layer structure. The substrate layer (B) has a plurality of through holes filled with a metal (4). The metal forms a continuous connection between the first metal layer (A) and the second metal layer (C). Figure 1B The substrate layer is shown in a top view in the current collector arrangement (B).
[0054] Arrangement 1 and Arrangement 2 may be present in the same battery.
[0055] The total thickness of the current collector of the present invention is preferably about 1 μm to about 12 μm, preferably about 2 μm to about 8 μm, and preferably about 4 μm to about 8 μm, preferably about 4 to about 6 μm.
[0056] Preferably, the current collector exhibits no more than about 2.0 Ω sq -1 , preferably not more than about 1.5Ωsq -1 , preferably not more than about 1.0Ωsq -1 Preferably, the current collector exhibits a sheet resistance of at least about 0.01 Ω sq -1 , preferably at least about 0.02Ωsq -1 , preferably at least about 0.05Ωsq -1 The preferred current collector exhibits a sheet resistance of about 0.01Ωsq -1 to about 2.0Ωsq -1 , preferably about 0.02Ωsq -1 to about 2.0Ωsq -1 , preferably about 0.02Ωsq -1 to about 1.5Ωsq -1 , preferably about 0.05Ωsq-1 To about 1.0Ωsq -1 Sheet resistance.
[0057] Preferably, the current collector exhibits a breakdown current of no more than about 35 A, preferably no more than about 30 A, preferably no more than about 20 A, preferably no more than about 10 A, preferably no more than about 5 A. Preferably, the current collector exhibits a breakdown temperature of no more than 300° C., preferably no more than about 250° C., preferably no more than about 240° C., preferably no more than about 230° C., and preferably no more than about 220° C. In a preferred embodiment, the breakdown temperature does not exceed the crystalline melting point (T M ), and generally corresponds to the point at which the polymer layer begins to shrink. Thus, when the polymer substrate layer is a PEN film, the current collector preferably exhibits a breakdown temperature of no more than about 270°C, preferably no more than about 260°C, preferably no more than about 250°C, preferably no more than about 220°C. When the polymer substrate layer is a PET film, the current collector preferably exhibits a breakdown temperature of no more than about 260°C, preferably no more than about 250°C, preferably no more than about 220°C. The breakdown current and temperature correspond to the point at which the current collector fails, i.e., the point at which the film acts as an electrochemical fuse to successfully prevent the risk of excessive current and heat propagation in the battery.
[0058] Preferably, the adhesion strength between the metal layer and the polymer substrate layer is at least 600 g / 25 mm, preferably at least about 700 g / 25 mm, preferably at least about 800 g / 25 mm.
[0059] According to a second aspect of the present invention, there is provided a method for manufacturing a current collector as described herein, wherein the method comprises the following steps:
[0060] (i) forming a biaxially oriented polymer substrate layer; and
[0061] (ii) depositing a metal on the first surface of the base layer to form a first metal layer.
[0062] Preferably, the method further comprises the following steps
[0063] (iii) depositing a metal on the second surface of the base layer to form a second metal layer;
[0064] The layer sequence is such that first metal layer / polymer substrate layer / second metal layer.
[0065] Before applying the metal layer, if necessary, the exposed surface of the biaxially oriented polymer substrate layer can be subjected to a chemical or physical surface modification treatment to improve the bonding between the polymer substrate layer and the subsequently applied layer. It is particularly advantageous to subject the exposed surface of the polymer substrate layer to such a treatment before depositing the metal layer.
[0066] The preferred treatment is to perform plasma treatment on the exposed surface of the substrate layer. Plasma treatment includes exposing the surface to a discharge caused and maintained by applying a high voltage in a low-pressure gas atmosphere, i.e., a so-called glow discharge. The surface is treated with activated particles of electrons, ions, excited atoms, excited molecules, free radicals, and ultraviolet rays formed during this glow discharge. One or more reagents known in the art can be injected into the glow discharge and injected onto the substrate. One or more reagents can be deposited to form a coating on the exposed surface. Known reagents include organic molecules, inorganic molecules, and biomolecules. Preferred reagents include a mixture of acrylic acid and methacrylic anhydride, (3-glycidyloxypropyl) trimethoxysilane, N-(3-trimethoxysilylpropyl) diethylenetriamine, or (3-mercaptopropyl) trimethoxysilane. For example, a suitable mixture of acrylic acid and methacrylic anhydride includes a mixture containing 75% by weight of acrylic acid and 25% by weight of methacrylic anhydride or a mixture containing 50% by weight of acrylic acid and 50% by weight of methacrylic anhydride.
[0067] The preferred plasma treatment is a corona treatment (sometimes referred to as air plasma), in which the exposed surface of the polymer substrate layer is subjected to a high voltage electrical stress accompanied by a corona discharge. The preferred treatment by corona discharge can be implemented in air at atmospheric pressure with conventional equipment using a high frequency high voltage generator, preferably with a power output of 1 to 20 kW at a potential of 1 to 100 kV. The discharge is conventionally achieved by passing the film through a dielectric support roller at a discharge station at a linear speed of preferably 1.0 to 500 m per minute. The discharge electrode can be positioned 0.1 to 10.0 mm from the moving film surface.
[0068] After plasma treatment, the polymer substrate layer preferably exhibits a water contact angle of no more than about 70°, preferably no more than about 65°, preferably no more than about 60°. After plasma treatment, the polymer substrate layer preferably exhibits a water contact angle of at least about 5°, preferably at least about 10°, preferably at least about 14°. Preferably, after plasma treatment, the polymer substrate layer exhibits a water contact angle of about 5° to about 70°, preferably about 10° to about 65°, preferably about 14° to about 60°.
[0069] The water contact angle between a HPLC grade water droplet and a polymer substrate layer can be measured using a Surface Analyst 3001 (BTG Labs).
[0070] After plasma treatment, the polymer substrate layer preferably exhibits a surface energy of about 30 to about 100 mN / m, preferably about 30 to about 80 mN / m. The surface energy can be measured by ink-based surface energy tests, such as the dyne level test according to ISO 8296.
[0071] The description and preferences of the first aspect apply equally to the second aspect.
[0072] According to the third aspect of the present invention, there is provided the use of a biaxially oriented polymer film as a substrate in a current collector, the current collector further comprising a first metal layer, wherein the use is for imparting improved adhesion strength and / or anti-delamination properties between the substrate and the metal layer, and wherein the biaxially oriented polymer substrate layer exhibits positive thermal expansion in each of the transverse direction (TD) and the machine direction (MD) at 200°C in air, wherein the polymer substrate layer has a thickness of not more than 12 μm, and wherein the first metal layer has a thickness of not more than 1000 nm.
[0073] Preferably, the current collector further comprises a second metal layer, wherein the current collector layer sequence is first metal layer / polymer substrate layer / second metal layer, and wherein the second metal layer has a thickness of no more than 1000 nm.
[0074] The descriptions and preferences of the first and second aspects apply equally to the third aspect.
[0075] According to a fourth aspect of the present invention, there is provided a battery comprising an anode material, an anode current collector, a cathode material, a cathode current collector and a separator between the anode material and the cathode material, wherein at least one of the current collectors is a current collector as described herein.
[0076] The battery may be selected from a lithium ion battery, a lithium sulfur (LiS) battery, a lithium air (LiO2) battery or a sodium ion battery. Preferably, the battery is a lithium ion battery, a lithium sulfur (LiS) battery or a lithium air (LiO2) battery. Preferably, the battery is a lithium ion battery. Preferably, the battery is a sodium ion battery.
[0077] Any suitable anode material, cathode material, and separator conventional in the art may be used.
[0078] The anode material may be selected from graphite and / or lithium titanate (LTO).
[0079] The cathode material may be selected from lithium or mixed oxides of lithium and other metals, in particular lithium titanate (LTO), lithium iron phosphate (LiFePO4, also known as LFP) and / or lithium-nickel-manganese-cobalt oxide (LiNiMnCoO2, also known as NMC).
[0080] The separator can be a polymer, ceramic, nonwoven or fabric separator. Suitable polymer separators are disclosed in, for example, WO-2019 / 186173-A and WO-2021 / 064359-A, the disclosures of which are incorporated herein by reference.
[0081] The battery, preferably a lithium ion battery, may further comprise an electrolyte. Where present, the electrolyte is preferably a conductive organic solvent that can saturate the other materials present in the battery, thereby providing a mechanism for the conduction of ions between the anode and cathode.
[0082] Alternatively, the battery (preferably a lithium ion battery) may be a dry core battery. A dry core battery contains a solid separator between the anode material and the cathode material, wherein the separator acts as both a separator and an electrolyte. In this way, a liquid electrolyte is excluded.
[0083] In the embodiment of arrangement 1 as described above, the current collector further comprises at least one conductive tab connecting the first metal layer and the second metal layer so that the current collector exhibits conductivity from one surface to the other surface thereof. Preferably, the tab extends beyond the periphery of the current collector so that the tab can connect the current collector to other components within the battery. Preferably, the tab extends from the interior to the exterior of the battery so that the tab can connect the battery to an external power source.
[0084] Preferably, the electrode material is coated or otherwise deposited onto the current collector.
[0085] The batteries, preferably lithium ion batteries, can have any configuration known in the art, including cans, pouch cells, prismatic cells, coin cells, cylindrical cells, wound prismatic cells, and wound pouch cells.
[0086] The descriptions and preferences of the first to third aspects also apply to the fourth aspect.
[0087] According to a fifth aspect of the present invention, there is provided use of a current collector as described herein in a battery (preferably a lithium ion battery) as described herein.
[0088] The descriptions and preferences of the first to fourth aspects also apply to the fifth aspect.
[0089] According to a sixth aspect of the present invention, there is provided a method for manufacturing a battery (preferably a lithium ion battery) as described herein, the method comprising the steps of:
[0090] (i) preparing a current collector as described herein;
[0091] (ii) assembling a battery (preferably a lithium ion battery), wherein the battery comprises an anode material, a cathode material, a separator between the anode material and the cathode material, an anode current collector and a cathode current collector, wherein at least one of the current collectors is the current collector obtained from step (i).
[0092] Preferably, the anode or cathode material may be coated or otherwise deposited onto the current collector described herein using any suitable coating or deposition technique conventionally used in the art for electrode preparation. It will be appreciated that the anode material is coated or otherwise deposited onto the outer surface of the metal layer of the anode current collector, while the cathode material is coated or otherwise deposited onto the outer surface of the metal layer of the cathode current collector. High processing temperatures (e.g., about 200° C.) are used during this coating or deposition step. In a preferred embodiment, the electrode material is coated onto the current collector.
[0093] The electrode / current collector assembly is suitably dried at a temperature of about 50° C. to about 170° C., preferably about 80° C. to 160° C. It will be appreciated that the drying step may include various temperature zones including appropriate heating profiles.
[0094] The dried electrode / current collector assembly is preferably compacted, for example, by calendering between a pair of rotating rollers. During calendering, the assembly may be exposed to electrostatic discharge and cleaned, for example, by a brush or air stream. Optionally, all or part of the compacting step may be heated, for example, to a temperature of about 50° C. to about 250° C., for example, by a preheating section and / or rollers during calendering.
[0095] The descriptions and preferences of the first to fifth aspects also apply to the sixth aspect.
[0096] As described below, the present invention is further illustrated with reference to the accompanying drawings.
[0097] FIG. 1 shows an assembly of a current collector according to Arrangement 2 as described above. Figure 1A The current collector is shown in cross section. Figure 1B The substrate layer is shown in a top view in the current collector arrangement (B).
[0098] Figure 2A , B, and C show TGA graphs of thermal relaxation between about 25°C and about 200°C for each of Examples 5 to 7 as described below.
[0099] Performance Measurement
[0100] The following test methods were used to characterize the performance of the current collectors and batteries described herein.
[0101] (i) Expansion of the biaxially oriented polymer layer
[0102] Thermomechanical analysis was performed on samples of biaxially oriented polymer layers with dimensions of 5 mm x 8 mm using a thermomechanical analyzer (TMA Q400 from TA Instruments Inc.). The longer dimension of the sample (i.e., the 8 mm dimension) corresponds to the sample direction for testing expansion. The sample was mounted on the apparatus and subjected to 1 N / mm in the machine direction (MD) or in the transverse direction (TD). 2 The thermal expansion at a temperature of 200°C in air is measured. The thermal expansion at 200°C in air is defined as the % change in the dimension of the film in a given direction (i.e., in MD or TD) and is calculated as (L1-L0) / L0 x 100, where L0 is the dimension at 32°C and L1 is the dimension at 200°C. As the skilled person will appreciate, negative thermal expansion indicates thermal contraction.
[0103] (ii) Coefficient of linear thermal expansion (CLTE)
[0104] A similar procedure to that of (i) was used. For the coefficient of linear thermal expansion measurement (b), the CLTE value was obtained from the following formula:
[0105] CLTE = (L1-L0) / (L0 x (T2-T1))
[0106] Where (L1-L0) is the change in sample length measured over the temperature range (T2-T1), and L0 is the original sample length at 32° C. Suitably, T2 is 200° C., and T1 is 32° C. The data may be plotted as a function of % change in sample length over temperature, normalized to 32° C.
[0107] (iii) Sheet resistance
[0108] The sheet resistance of the conductive layer was measured using a linear four-point probe (Jandel Model RM2) according to ASTM F390-98 (2003).
[0109] (iv) Breakdown current and breakdown temperature
[0110] A current collector sample measuring 50 mm x 10 mm is clamped between a pair of conductive clips at each end. The sample is clamped so that there is 10 mm of 2 The sample is held in the clamp. Current is passed through the sample at a ramp rate of 2A / min until breakdown is observed. The temperature profile of the sample is monitored throughout the test using a thermal imaging camera in order to determine the temperature at breakdown.
[0111] (v) Adhesion strength of current collector
[0112] The adhesion strength of the metallized polymer substrate to EAA (ethylene acrylic acid film) having a thickness of 25 μm (commercially available as Vistafix (TP) from UCB Sidac Division) was evaluated as follows. The samples of the current collector and the samples of the EAA film were placed together so that the outer surface of the metallized polymer substrate layer was in contact with the surface of the EAA film. The samples were heat sealed using a Sentinel Model 12 (Packaging Industries Group Inc) machine under the following conditions: 105°C (upper jaw) and 25°C (lower jaw), at a pressure of 50psi for 10 seconds. The sealed samples were cut into 25mm wide strips and the adhesion strength was determined using an Instron Model 4464. The jaws were set to 50mm apart. The upper jaws clamped the EAA sheet of the sealed sample and moved upward at a speed of 300mm / min, while the lower jaws clamped the current collector sheet of the sealed sample and remained stationary. The average peel force was measured and reported as the average of 5 results. The plane of adhesion failure was also noted.
[0113] When the adhesion strength between the metal layer and the polymer substrate layer is lower than the adhesion strength between the metal layer and the EEA film (about 800 g / 25 mm), the test sample is delaminated along the interface between the metal layer and the polymer substrate layer. In this case, the average peel force represents the adhesion strength between the metal layer and the polymer substrate layer.
[0114] When the adhesion strength between the metal layer and the polymer substrate layer was higher than the adhesion strength between the metal layer and the EEA film (800 g / 25 mm), the test sample was delaminated along the interface of the metal layer and the EEA film.
[0115] A further failure plane is cohesive failure within the metallization layer itself, which also indicates that the adhesion strength between the metal layer and the polymer substrate layer is greater than the force required to reach cohesive failure (thus typically the adhesion strength between the metal layer and the polymer substrate layer is greater than about 800g / 25mm).
[0116] (vi) Anti-delamination of current collector
[0117] The delamination resistance was evaluated by subjecting the current collector to elevated temperatures by placing it in a heating oven at that temperature, i.e., at 200°C for 5 or 10 minutes, followed by 130°C for the same period of 5 or 10 minutes. The adhesion strength was measured according to the method described above before and after the heat treatment to evaluate the delamination resistance of the current collector after exposure to elevated temperature conditions, which represent the conditions used during a typical battery manufacturing process. Delamination resistance is defined as:
[0118] Delamination resistance = 100*((A TT –A0) / A0)
[0119] in:
[0120] A TT = Adhesion strength of current collector after heat treatment
[0121] A0 = Adhesion strength of current collector before heat treatment
[0122] experiment
[0123] Experiment 1
[0124] The performance of the current collector according to the present invention having a first and a second metal (Cu or Al) layer on a polyester (PET or PEN) film substrate was studied using the form and specifications of commercially available batteries. The current collector has an ABC layer structure, wherein layer A is the first metal layer, layer B is the polyester film substrate, and layer C is the second metal layer. The thickness of each metal layer is 150nm. The thickness of the polyester film substrate is 6μm. The performance is compared with a current collector consisting of a metal foil (Cu or Al) with a thickness of 12μm.
[0125] Four commercially available lithium-ion batteries were considered, according to the supplier's specifications. Example 1 was based on A123 pouch cells for Chevrolet Spark EV (2012) with C / LFP cell chemistry at 3.3V and 20Ah. Example 2 was based on Toshiba SciB high power cells with LTO / NMC cell chemistry at 2.4V and 2.9Ah. Example 3 was based on A123 cylindrical 18650 cells with C / LFP cell chemistry at 3.3V and 1.2Ah. Example 4 was based on cylindrical 21700 cells with C / NMC cell chemistry at 3.9V and 3.8Ah.
[0126] The cell mass, energy density and power density of each commercial cell including the current collector of the present invention (Examples 1-4) or the conventional foil current collector (Comparative Examples 1-4) were measured. The results are shown in Table 1 (wherein "n / m" means "not measured").
[0127] As demonstrated by the data in Table 1, the current collectors of the present invention are capable of forming batteries with significantly reduced mass compared to batteries made with conventional current collectors composed of metal foil. Thus, lithium ion batteries with reduced mass, improved energy density, and improved power density can be produced using the current collectors of the present invention.
[0128] Table 1
[0129]
[0130] Experiment 2
[0131] A series of biaxially oriented films were prepared to determine the effect of post-stretching heat treatment on thermal expansion. Comparative Example 5, Example 7 and Example 16 are PET films each having a thickness of 6 μm. Comparative Example 6 is a PEN film having a thickness of 6 μm. The films were stretched simultaneously in MD and TD using the stretch ratios shown in Table 2. The biaxially stretched films were then annealed under dimensional restraint and then relaxed in MD and TD according to the conditions shown in Table 2. Two relaxation steps were performed for Comparative Example 5, Example 7 and Example 16, while one relaxation step was performed for Comparative Example 6. The thermal expansion of each film at 200°C in air and the linear thermal expansion coefficient in both MD and TD were evaluated, and the results are shown in Table 2 (where "n / m" means "not measured"). Negative values for thermal expansion indicate shrinkage. The thermal expansion diagrams of Examples 5 to 7 between 32°C and 200°C are shown in Table 2, respectively. Figure 2A-2C middle.
[0132] Table 2
[0133]
[0134] As shown in Table 2 and Figure 2, the thermal expansion behavior of the film is a function of the degree of relaxation and the temperature used during the relaxation step. For example, the film of Comparative Example 5 ( Figure 2A ) exhibits TD expansion below about 180°C (which corresponds to the highest temperature employed during the TD relaxation step) and then exhibits TD contraction at higher temperatures. In contrast, the film of Example 7 ( Figure 2C The films of Example 10 and Example 16 exhibit TD expansion at 200 °C because higher temperatures were used during the TD relaxation step.
[0135] In addition, the film of Comparative Example 5 exhibited negative CLTE in TD and MD in the range of 32°C to 200°C, respectively, because the film exhibited TD and MD shrinkage at higher temperatures. Figure 2C ) advantageously exhibits positive CLTE in each of TD and MD in the range of 32°C to 200°C because the film exhibits TD and MD expansion over this temperature range (including at higher temperatures of 200°C).
[0136] Experiment 3
[0137] A series of current collectors are prepared by metallizing a series of biaxially oriented polyester films. The polymer and thickness of the biaxially oriented substrate are shown in Table 3. Before depositing the metal layer, the biaxially oriented film is stretched simultaneously in MD and TD using the stretch ratio shown in Table 3, and then relaxed in MD and TD using the conditions shown in Table 3 (wherein "-" indicates that the film does not undergo the relaxation step). The total duration of the relaxation step is between 0.4 and 4.7 seconds. Then an Al metal layer (as shown in Table 3) with a thickness of 40 to 91nm is deposited on the first surface of the biaxially oriented substrate. For each of Comparative Examples 8-9 and Examples 11-12, an Al second metal layer having the same thickness as the first metal layer is then deposited on the second surface of the biaxially oriented substrate to obtain a current collector having an ABC layer structure, wherein layer A is the first metal layer, layer B is a polyester film substrate, and layer C is the second metal layer. The thermal expansion of the film in air at 200°C in MD and TD and the anti-delamination of the current collector are measured as described herein, and the results are shown in Table 3.
[0138] Table 3
[0139]
[0140] As demonstrated by the data in Table 3, current collectors in which the substrate layers each exhibit positive thermal expansion in MD and TD provide unexpectedly improved resistance to delamination when exposed to elevated temperatures. The films of Examples 11 and 12 each exhibit positive MD and TD expansion at 200°C and provide unexpectedly improved resistance to delamination. In particular, the adhesion strength of the films was unexpectedly retained after exposure to elevated temperatures, as the reduction in adhesion strength was very small. Therefore, overall, the degree of adhesion observed after exposure to elevated temperatures remained high. In contrast, the films of Comparative Examples 8 to 10 each exhibited at least MD shrinkage at 200°C and exhibited poor resistance to delamination, as at least 45% of the original adhesion strength was lost after exposure to elevated temperatures.
[0141] The sheet resistance of the film of Comparative Example 10 was measured as described herein. The sheet resistance was found to be between 0.9 and 2 Ω sq -1 Therefore, the current collector exhibits good sheet resistance. In particular, the current collector with a higher metal layer thickness of about 88 nm advantageously achieves less than 1Ωsq -1 Sheet resistance.
[0142] Reference experiment 4
[0143] A preliminary series of current collectors were prepared using a PEN polyester base layer and a first and second Cu metal layer. The biaxially oriented PEN polyester film had a thickness of 6 μm. The film was stretched simultaneously in MD and TD with an MD stretch ratio of 3.35 and a TD stretch ratio of 3.55. The biaxially oriented PEN polyester film was then annealed under dimensional restraint and subjected to a TD relaxation of -1% at a temperature of 190°C for 2.8 seconds. The thermal expansion of the film in air at 200°C in MD and TD was measured as described herein and the results were -0.45 and 0.18, respectively.
[0144] The first and second Cu metal layers were deposited on a biaxially oriented PEN polyester film using the virtual cathode deposition process described above to obtain Comparative Examples 13 and 14. Comparative Example 15 is a conventional metal foil made of Cu. Table 4 shows the thickness as well as the through-film resistance (R), sheet resistance (sheet R), breakdown current, and breakdown temperature measured as described herein.
[0145] Table 4
[0146]
[0147] The results in Table 4 demonstrate that the metallized polymer film based current collector advantageously exhibits lower breakdown current and breakdown temperature than conventional metal foil current collectors, thereby preventing excessive current during use, thereby minimizing the risk of short circuits or heat propagation. The sheet resistance is low enough to allow good conductivity within the plane of the copper layer.
Claims
1. A current collector comprising a biaxially oriented polyester base layer, a first metal layer on one side of the polyester base layer, and a second metal layer, wherein the first metal layer and the second metal layer are on opposite sides of the polyester base layer, wherein the polyester base layer exhibits positive thermal expansion in each of a transverse direction (TD) and a machine direction (MD) at 200° C. in air, wherein the polyester base layer has a thickness of no more than 12 μm, wherein the first metal layer has a thickness of no more than 1000 nm, and wherein the second metal layer independently has a thickness of no more than 1000 nm; wherein the thermal expansion at 200°C in air is defined as the % change in the size of the sample in the machine direction (MD) or the transverse direction (TD) and is calculated as (L1-L0) / L0 x100, wherein L0 is the size at 32°C and L1 is the size at 200°C, and wherein, The thermal expansion is measured under the following conditions: the sample is subjected to 1 N / mm in the machine direction or in the transverse direction. 2 of load and a heating rate of 10°C / min from 32°C to 220°C. 2 . The current collector according to claim 1 , wherein the polyester base layer has a thickness of 1.0 to 12.0 μm. 3 . The current collector according to claim 1 , wherein the polyester is polyethylene terephthalate or polyethylene naphthalate.
4. The current collector according to claim 1 or 2, wherein the polyester base layer exhibits a thermal expansion of greater than 0% to no more than 3.0% in each of the transverse direction (TD) and the machine direction (MD) at 200°C in air.
5. The current collector according to claim 1 or 2, wherein the polyester base layer exhibits a positive linear thermal expansion coefficient (CLTE) in each of the transverse direction (TD) and the machine direction (MD) in the range of 32°C to 200°C; wherein the coefficient of linear thermal expansion (CLTE) is calculated as (L1-L0) / (L0 x(T2-T1)), wherein L1-L0 is the change in length of the sample measured over the temperature range T2-T1, wherein L1 is the length at 200°C, L0 is the length at 32°C, T2 is 200°C, and T1 is 32°C, and wherein, The coefficient of linear thermal expansion (CLTE) is measured under the following conditions: the sample is subjected to 1 N / mm in the machine direction or in the transverse direction. 2 of load and a heating rate of 10°C / min from 32°C to 220°C. 6 . The current collector according to claim 1 , wherein the thickness of the first metal layer (A) and the second metal layer (C) are each independently 50 nm to 1000 nm.
7. A current collector according to claim 1 or 2, wherein the first metal layer (A) and the second metal layer (C) each independently exhibit an isotropic thermal expansion of greater than 0% to no more than 1.0% at 200°C in air, wherein isotropic thermal expansion means that each layer expands the same amount in orthogonal directions.
8. The current collector according to claim 1 or 2, wherein the first metal layer (A) and the second metal layer (C) each independently exhibit a 10×10 -6 / ℃ to 30x 10 -6 / °C positive linear thermal expansion coefficient (CLTE), wherein the linear thermal expansion coefficient (CLTE) is calculated as (L1-L0) / (L0 x(T2-T1)), wherein (L1-L0) is the change in length of the sample measured in the temperature range T2-T1, wherein L1 is the length at 100°C, L0 is the length at 32°C, T2 is 100°C, and T1 is 32°C, and wherein, The coefficient of linear thermal expansion (CLTE) is measured under the following conditions: the sample is subjected to 1 N / mm in the machine direction or in the transverse direction. 2 of load and a heating rate of 10°C / min from 32°C to 220°C.
9. The current collector according to claim 1 or 2, wherein the first metal layer (A) and the second metal layer (C) each independently comprise at least one of aluminum, copper, nickel, titanium, silver, a nickel-copper alloy, or an aluminum-zirconium alloy. 10 . The current collector according to claim 1 , wherein the first metal layer and the second metal layer are both aluminum or copper. 11 . The current collector according to claim 1 or 2 , wherein the adhesion strength between the metal layer and the polyester base layer is at least 600 g / 25 mm, wherein the adhesion strength is measured using an Instron model 4464.
12. The current collector according to claim 1 or 2, which exhibits a 0.01Ωsq -1 To 2.0Ωsq -1 The sheet resistance is measured according to ASTM F390-98 (2003) using a linear four-point probe Jandel model RM2.
13. The current collector according to claim 1 or 2, wherein the current collector exhibits a breakdown current of no more than 30A and / or a breakdown temperature of no more than 300°C, wherein the breakdown current and the breakdown temperature are measured under the following conditions: a current is passed through the sample at a ramp rate of 2A / min until breakdown is observed. 14 . The current collector according to claim 1 , further comprising at least one tab connecting the first metal layer and the second metal layer.
15. A current collector according to claim 1 or 2, wherein the polyester base layer comprises a channel extending from a first surface thereof to a second opposite surface, wherein (i) the sides of the channel are at least partially coated with at least one metal, and / or (ii) the channel is at least partially filled with at least one metal.
16. A method for manufacturing a current collector as defined in any one of claims 1 to 15, wherein the method comprises the following steps: (i) forming a biaxially oriented polyester base layer; as well as (ii) depositing a metal on the first surface of the base layer to form a first metal layer; as well as (iii) depositing a metal on the second surface of the base layer to form a second metal layer; The layer sequence is such that first metal layer / polymer substrate layer / second metal layer.
17. A method according to claim 16 wherein step (i) comprises extruding a layer of molten polyester and biaxially stretching the extrudate at a temperature above the glass transition temperature of the polyester.
18. A method according to claim 16 or claim 17, wherein step (i) comprises forming the polyester by sizing the polyester at a temperature above the glass transition temperature but below the melting temperature (T M ) to stabilize the dimensions of the biaxially stretched film.
19. The method according to claim 18, wherein step (i) comprises dimensional relaxation of the biaxially stretched film in both the transverse direction and the machine direction, and wherein the relaxation in each of the transverse direction and the machine direction is from 0.5 to 5.0%, so that when the method comprises the annealing step of claim 18, the dimensional relaxation is carried out thereafter.
20. The method of claim 19, wherein step (i) comprises a second relaxation step after the relaxation step of claim 19, wherein the second relaxation step is performed at a lower temperature than the relaxation step of claim 19.
21. The method according to claim 16 or 17, comprising subjecting the exposed surface of the polyester base layer to a surface modification treatment, wherein the treatment step is performed after step (i) and before step (ii).
22. The method according to claim 16 or 17, wherein step (ii) and / or step (iii) comprises depositing the metal using thermal evaporation deposition, electron beam evaporation deposition or virtual cathode deposition.
23. Use of a biaxially oriented polyester film as a substrate in a current collector, the current collector further comprising a first metal layer and a second metal layer, wherein the use is for imparting improved adhesion strength and delamination resistance between the substrate and the metal layer, and wherein the polyester substrate layer exhibits positive thermal expansion in each of the transverse direction (TD) and the machine direction (MD) at 200° C. in air, wherein the polyester substrate layer has a thickness of not more than 12 μm, wherein the first metal layer has a thickness of not more than 1000 nm, and wherein the second metal layer independently has a thickness of not more than 1000 nm and wherein the thermal expansion at 200°C in air is defined as the % change in the size of the sample in the machine direction (MD) or the transverse direction (TD) and is calculated as (L1-L0) / L0 x100, wherein L0 is the size at 32°C and L1 is the size at 200°C, and wherein, The thermal expansion is measured under the following conditions: the sample is subjected to 1 N / mm in the machine direction or in the transverse direction. 2 of load and a heating rate of 10°C / min from 32°C to 220°C.
24. A battery comprising an anode material, a cathode material, a separator between the anode material and the cathode material, an anode current collector and a cathode current collector, wherein at least one of the current collectors is a current collector defined in any one of claims 1 to 15.
25. The battery of claim 24, wherein the battery is a lithium ion battery.
26. The battery according to claim 24 or claim 25, wherein the anode material is coated on the anode current collector, and wherein the anode current collector is a current collector defined in any one of claims 1 to 15.
27. The battery according to claim 24 or 25, wherein the cathode material is coated on the cathode current collector, and wherein the cathode current collector is a current collector defined in any one of claims 1 to 15.
28. Use of a current collector as defined in any one of claims 1 to 15 in a battery as defined in claim 24, 25 or 26.
29. A method for manufacturing a battery as defined in any one of claims 24 to 27, the method comprising the steps of (i) preparing or obtaining a current collector as defined in any one of claims 1 to 15; (ii) assembling the battery, wherein the battery comprises an anode material, a cathode material, a separator between the anode material and the cathode material, an anode current collector and a cathode current collector, wherein at least one of the current collectors is the current collector obtained from step (i).
Citation Information
Patent Citations
Process for crystallization of polyethylene naphthalate
EP0419400A2
Method of manufacture of an energy storage device having an internal fuse
US10700339B2
Bi-axially stretched breathable film, process for making the same and use thereof
US20090117362A1
Current Collector, Electrode Plate Including The Same And Electrochemical Device
US20190305320A1
Carbon materials
US20200095129A1